Pengaruh Metode Mind Mapping Terhadap Kemampuan Menulis Karangan Narasi - Resnani Resnani; Hasnawati Hasnawati; Ilmi Nazarrotin (JURIDIKDAS, 2018)
This study aims to determine the effect of Mind Mapping method on the ability to write a narrative essay. This research is a quantitative research. The method in this research is quasi experimental method with The Matching Only Pretest-Posttest Control Group Design. The sample of the research was determined by total sampling technique in class IV elementary school number 51 Bengkulu city. The sample in this research is all the fourth grade students which consist of  IVA and IVB class amount to 49 students. Students of class IVB as experimental class and class IVA as control class. The instrument used is a test sheet provided through pretest and posttest. The data of this research are analyzed by descriptive and inferential statistic that is t-test. From the result of research known result of  t-test (3,148)> t table (2,01174) at 5% significant level. The value of tcount obtained is greater than t table value, it can be concluded that there is influence of  Mind Mapping method to the ability of writing essay writing.